Comparative analysis of the health level of Indonesian Sharia Banks and Bank Muamalat using the method Risk-Based Bank Rating - Sandra, Sahara; Rahayu, Sri; Ilmiha, Jalilah; Kurnia Ningsih, Heny Triastuti; Rangkuti, Lusi Elviani (Universiti Teknologi MARA, Perlis, 2025)
This study aims to examine the disparities in the financial health levels between Bank Syariah Indonesia and Bank Muamalat using the Risk-Based Bank Rating (RBBR) approach. A descriptive analysis was employed as the quantitative method for this research. For hypothesis testing, the Independent Sample T-Test was applied to normally distributed data, while the Mann-Whitney U-Test was used for nonnormally distributed data. The findings reveal that both banks fall under the "healthy" category based on their Non-Performing Financing (NPF) and Good Corporate Governance (GCG) ratios. However, Bank Muamalat shows a stronger Financing to Deposit Ratio (FDR) compared to Bank Syariah Indonesia. Conversely, Bank Syariah Indonesia demonstrates greater robustness in Return on Assets (ROA), Return on Equity (ROE), and Operating Expenses to Operating Income (BOPO) ratios. Both banks share an "exceptionally healthy" rating for their Capital Adequacy Ratio (CAR). Significant differences were found in the ROE and BOPO ratios between the two banks. However, no significant differences were observed in the NPF, FDR, ROA, CAR, or GCG ratios during the 2020–2022 period. Sahara Sandra, Sri Rahayu, Jalilah Ilmiha, Heny Triastuti Kurnia Ningsih, Lusi Elviani Rangkuti